Effects of Turmeric and Curcumin Dietary Supplementation on Human Gut Microbiota: A Double-Blind, Randomized, Placebo-Controlled Pilot Study - Christine T. Peterson PhD; Alexandra R. Vaughn PhD; Vandana Sharma PhD; Deepak Chopra MD; Paul J. Mills PhD; Scott N. Peterson PhD; Raja K. Sivamani MD (SAGE Publishing, 2018)
Background. Curcuma longa (common name: turmeric) and one of its biologically active constituents, curcumin, have received increased clinical attention. Insufficient data exist on the effects of curcumin and turmeric on the gut microbiota and such studies in humans are lacking. Methods. Turmeric tablets with extract of piperine (Bioperine) (n = 6), curcumin with Bioperine tablets (n = 5), or placebo tablets (n = 3) were provided to healthy human subjects and subsequent changes in the gut microbiota were determined by 16S rDNA sequencing. Results. The number of taxa detected ranged from 172 to 325 bacterial species. The placebo group displayed an overall reduction in species by 15%, whereas turmeric-treated subjects displayed a modest 7% increase in observed species posttreatment. Subjects taking curcumin displayed an average increase of 69% in detected species. The gut microbiota response to treatment was highly personalized, thus leading to responders and nonresponders displaying response concordance. These "responsive" subjects defined a signature involving uniform increases in most Clostridium spp., Bacteroides spp., Citrobacter spp., Cronobacter spp., Enterobacter spp., Enterococcus spp., Klebsiella spp., Parabacteroides spp., and Pseudomonas spp. Common to these subjects was the reduced relative abundance of several Blautia spp. and most Ruminococcus spp. Conclusions. All participants' microbiota displayed significant variation over time and individualized response to treatment. Among the responsive participants, both turmeric and curcumin altered the gut microbiota in a highly similar manner, suggesting that curcumin may drive the majority of observed changes observed in turmeric-treated subjects.